Rapid Synthesis of the X-linked Mental Retardation Protein OPHN1 Mediates mGluR-Dependent LTD through Interaction with the Endocytic Machinery - Nadif Kasri, Nael (2011)
Activation of group I metabotropic glutamate receptors leads to long-term depression (mGluR-LTD). Alterations in this form of plasticity have been linked to drug addiction and cognitive disorders. A key characteristic of mGluR-LTD is its dependence on rapid protein synthesis; however, the identities of the proteins mediating LTD remain elusive. Here, we identify the X-linked mental retardation protein OPHN1 as a molecule essential for mGluR-LTD in the hippocampus. mGluR-LTD induction elicits rapid dendritic OPHN1 synthesis, which is dependent on mGluR1 activation and independent of fragile X mental retardation protein (FMRP). This response is essential for mGluR-LTD, as acute blockade of OPHN1 synthesis impedes LTD. mGluR-induced OPHN1 mediates LTD and associated persistent decreases in surface AMPARs via interactions with Endophilin-A2/3. Importantly, this role of OPHN1 is separable from its effects on basal synaptic strength, which require OPHN1’s Rho-GAP activity and interaction with Homer1b/c. Thus, our data establish a novel role for rapid OPHN1 synthesis in mGluR-LTD.